Artificial cells as biotechnological devices that mimic the parameters of natural cells - Gapeeva, Tamara A. (Experimental Biology and Biotechnology, 2024)
The term «artificial cell» is widely used in scientific circles, but its understanding is ambiguous. The original concept of an artificial cell related to the idea of replacing the functions of natural cells by analogy with organ transplantation, rather than to recreate a living cell. Currently, the original concept does not encompass the entire variety of synthetic biology objects defined as artificial (synthetic) cells. The creation of artificial cells pursues three main goals related to the research of the question of the origin of life, the study of cell biology and the solution of practical problems in many fields, most notably medicine. Within the framework of reductionist approach used in science, artificial cells can be divided into two groups according to the way they are obtained: bottom-up cells (created according to the principle «from simple to complex») and top-down cells (created according to the principle «from complex to simple»). This review focuses on the bottom-up development and application of such cells, which can be defined as biotechnological devices that mimic the parameters of natural cells for use primarily in numerous practical applications.
Keywords: artificial cell; biotechnology; synthetic biology; cell membranes; natural cells mimicking